Vibration analysis of elevator traveling cable by ANCF considering internal damping - Takayoshi KAMADA; Yuki FUKAYAMA; Kazuhiro TANAKA; Tetsu OGAWA; Tomohiro SHIKI; Taku YOSHIDA (Mechanical Engineering Journal)
Traveling cables are important components for elevators that transmit electricity and control command to elevator car. In recent years, as buildings have become taller, traveling cables have also become longer. So, cables are easily oscillated by building swing caused by wind or earthquake, and vibration remains long time. It causes collision and entanglement with the devises in the hoistway. Normally, travelling cables are composed of wires covered by vinyl sheath and precise modelling is very difficult. In this paper, two modelling strategies especially for damping property of the cable are proposed using Absolute Nodal Coordinate Formulation (ANCF). ANCF is a kind of the finite element method (FEM) and is suitable for the analysis of the large displacement and deformation problems of flexible structures. One strategy is a combination of bending damping and internal viscous damping; the other is combination of viscoelastic damping modelled by the three elements Maxwell model and internal viscous damping. Deriving of the equations of motion with damping became simple by introducing the complementary element coordinate. Experiments were carried out for bending stiffness and damping parameters identification and swing behavior in lateral direction was observed. Simulation studies were conducted, and both strategies were useful in engineering to simulate the behavior of travelling cables.